2018
DOI: 10.3389/fmicb.2018.02167
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relatedness Among Plasmids Harbored by Campylobacter jejuni and Campylobacter coli Isolated From Retail Meats

Abstract: Campylobacter jejuni and Campylobacter coli are two of the major causes of foodborne illness. In this study, 29 plasmids isolated from 20 retail meat isolates of Campylobacter jejuni and Campylobacter coli were fully-sequenced individually or as a part of a whole genome sequencing approach. The fully-sequenced plasmids ranged in size from 3 to 119 kb. Molecular characterization of the sequenced plasmids was based on pangenomic analysis and types of genes present on these plasmids and similar ones from GenBank.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 42 publications
(105 reference statements)
3
29
0
Order By: Relevance
“…We previously demonstrated that Type 1 (pTet), Type 2 and Type 3 plasmids in Campylobacter spp. were primarily of C. jejuni/ coli origin 14 . However, further analyses with additional megaplasmid sequences is needed to conclusively show species-specific clustering since only seven megaplasmid sequences were used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that Type 1 (pTet), Type 2 and Type 3 plasmids in Campylobacter spp. were primarily of C. jejuni/ coli origin 14 . However, further analyses with additional megaplasmid sequences is needed to conclusively show species-specific clustering since only seven megaplasmid sequences were used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter spp. harbor plasmids that vary in size 14 ; however, few Campylobacter strains possess megaplasmids 13 , 22 , 23 . The megaplasmids characterized in this study, pCJDM202 and pCJDM67L, are similar to the pTet plasmids and encode conserved proteins for conjugation and the T4SS 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the sequence revealed it to correspond to a not yet described class of tetracycline-resistant gene that presents a mosaic structure with the replacement of the 776-1127 bp internal fragment of tet(O) by the homologous sequence from tet(M) (Figure 2). This tet(O/M/O) mosaic gene might have evolved from a homologous recombination event between tet(O) and tet(M), encoding a ribosomal protection factor widely spread in Firmicutes from the Bacilli class, such as enterococci and streptococci [26,27,35,36], many of which share the mammalian gastrointestinal tract environment with Campylobacter, which, together with Megasphaera and Riemerella, are the only three Gram-negative genera in which tet mosaic genes have been reported [13]. Curiously, all these genera are common inhabitants of the gastrointestinal tract of both animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports indicating the presence of tet(O) either on plasmid or chromosome (Pratt and Korolik, 2005;Dasti et al, 2007), we found that 30 and 9 of the analyzed genomes carry this resistance gene on plasmid and chromosome, respectively ( Table 1). It should be noted that Campylobacter plasmids are usually classified according to the genes they carry, those harboring the tet(O) gene have been called pTet plasmids (Marasini et al, 2018). From 87 plasmids annotated as an assembly unit separated from chromosome in the total of Campylobacter genomes tested, 30 were pTet and only one plasmid containing an AR gene other than tet(O) was found; the 31 plasmids harboring AR genes show sizes ranging from 29,115 to 180,543 bp ( Figure 2).…”
Section: Identification Of Genetic Determinants Associated With Ar Inmentioning
confidence: 99%